Cultural connections between Anatolia and Caucasus-Central Asia during the late bronze-early iron age : in the light of the 1987 Sos Höyük excavations and north-eastern Turkey surveys, carried out between 1985-1997. - Güneri, A. Semih. ([İstanbul ; Paris])
11-77 ss.